Remote Pediatric Ophthalmology and Adult Strabismus during the COVID-19 Pandemic. Issue 3 (3rd July 2021) - Christoff, Alex; Guo, Xinxing; Repka, Michael X.
ABSTRACT: Background: The coronavirus (COVID-19) global pandemic has been a poignant reminder of the value of telehealth services to deliver care, especially as a means of reducing the risk of infectious disease transmission caused by close personal contact, decreasing unnecessary travel for medical consultations, and limiting the number of individuals in waiting rooms. The role of telehealth in ophthalmology has historically been limited to store-and-forwarding of images, much like what is used in radiology. Patients and Methods: Remote evaluation using two-way audio-video communications over the initial 10-week period of clinic shutdowns. Visual acuity (VA) measurement was attempted using a printed single surrounded HOTV or Snellen chart. The VA measurement of fellow eyes was compared to the prior in person clinical visit. External and strabismus examinations were also conducted Results: Fifty-eight patients were evaluated with a mean age 12.5 years (range 5 months to 82 years). Twenty of 58 (34%) were younger than 5 years of age. Reasons for evaluation were strabismus in 26 patients (45%), refractive error in 25 (43%), and amblyopia in 10 patients (19%). Recognition visual acuity was obtained in 69% (40 of 58), including every patient older than 5 years of age. Nine children from 2 to 5 years of age (mean 3 years) were unable to perform HOTV VA testing. Of nine children unable to do complete VA testing, five had been premature and seven had developmental delay. There was a mean bias of −0.12 logMAR in favor of the prior in office test in the right eyes of 21 non-amblyopic patients. The 95% limits of agreement between the in-person visit and the subsequent telehealth video visit logMAR VA were +0.20 logMAR upper limit, −0.44 logMAR lower limit. Conclusions: Telehealth video visits provided basic ophthalmic information in patients who are physically incapable to come to the office, leading to improved triage. Vision could be tested remotely in young children, but we found substantial variability in the measurement of clinically normal eyes. Improvements in the reliability of at-home visual acuity testing are needed.